2010
DOI: 10.1128/ec.00364-09
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Engineering of Algae for Enhanced Biofuel Production

Abstract: 2There are currently intensive global research efforts aimed at increasing and modifying the accumulation of lipids, alcohols, hydrocarbons, polysaccharides, and other energy storage compounds in photosynthetic organisms, yeast, and bacteria through genetic engineering. Many improvements have been realized, including increased lipid and carbohydrate production, improved H 2 yields, and the diversion of central metabolic intermediates into fungible biofuels. Photosynthetic microorganisms are attracting consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
577
0
10

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 978 publications
(589 citation statements)
references
References 218 publications
(193 reference statements)
2
577
0
10
Order By: Relevance
“…A more complete understanding of the significance of transcriptional control of cellular processes is important for an improved understanding of the basic biology of diatoms and other microalgae, and has implications for environmental and biotechnological studies. For example, metabolic engineering to improve lipid productivity is widely considered to be an essential element of economic feasibility and commercialization of algae as a feedstock for renewable biofuels (Radakovits et al ., 2010; Davis et al ., 2011). Appropriate selection of targets for effective genetic engineering is required to accomplish these tasks.…”
Section: Introductionmentioning
confidence: 99%
“…A more complete understanding of the significance of transcriptional control of cellular processes is important for an improved understanding of the basic biology of diatoms and other microalgae, and has implications for environmental and biotechnological studies. For example, metabolic engineering to improve lipid productivity is widely considered to be an essential element of economic feasibility and commercialization of algae as a feedstock for renewable biofuels (Radakovits et al ., 2010; Davis et al ., 2011). Appropriate selection of targets for effective genetic engineering is required to accomplish these tasks.…”
Section: Introductionmentioning
confidence: 99%
“… The ability to thrive in diverse ecosystems Although microalgae have long been considered a promising feedstock for the production of biofuels, studies have concluded that the economic viability of microalgal biofuel production is in need of significant improvement. However, in contrast to previous efforts, we are now equipped with an arsenal of new genetic tools, genome sequences, and high-throughput analytical techniques that will equip and empower scientists to analyze and manipulate metabolic pathways with unrivaled precision [6].…”
Section: Discussionmentioning
confidence: 99%
“…They are an extremely diverse group of organisms, many of which possess unique metabolic features that can be altered for the production of renewable biofuels [6]. These include:  High efficiency of conversion during photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations